The significance of the fusion partner gene genomic neighborhood analysis in translocation-defined tumors - Mosaieby, Elaheh; Martínek, Petr; Ondič, Ondrej (Molecular genetics & genomic medicine, 2022)
INTRODUCTION: This study presents a novel molecular parameter potentially co-defining tumor biology-the total tumor suppressor gene (TSG) count at chromosomal loci harboring genes rearranged in fusion-defined tumors. It belongs to the family of molecular parameters created using a black-box approach. METHOD: It is based on a public curated Texas TSG database. Its data are regrouped based on individual genes loci using another public database (Genecards). The total TSG count for NTRK (NTRK1; OMIM: 191315; NTRK2; OMIM: 600456; NTRK3; OMIM: 191316), NRG1 (OMIM: 142445), and RET (OMIM: 164761) rearranged tumors in patients treated with a theranostic approach is calculated using the results of recently published studies. RESULTS: Altogether 138 loci containing at least three TSGs are identified. These include 21 "extremely hot" spots, with 10 to 28 TSGs mapping to a given locus. However, the study falls short of finding a correlation between tumor regression or patient survival and the TSG count owing to a low number of cases meeting the study criteria. CONCLUSION: The total TSG count alone cannot predict the biology of translocation-defined tumors. The addition of other parameters, including microsatellite instability (MSI), tumor mutation burden (TMB), homologous recombination repair deficiency (HRD), and copy number heterogeneity (CNH), might be helpful. Thus a multi-modal data integration is advocated. We believe that large scale studies should evaluate the significance and value of the total TSG count.
Keywords: mutace; cancer; tumor mutation burden; gene; chromosomal instability; Neoplasms; nádory; microsatellite instability; chromothripsis; Genomics; lidé; translocation; Gene Fusion; Mutation; copy number heterogeneity; gene rearrangement; Humans; nádorové biomarkery; artificial intelligence; homologous recombination repair; tumor suppressor gene; fúze genů; Biomarkers, Tumor; translokace genetická; genomika; Translocation, Genetic